2020
DOI: 10.7150/jca.34723
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of circulating microRNA in four sarcoma subtypes

Abstract: Background: Sarcomas are rare malignant tumors of mesenchymal origin. The discovery of circulating biomarkers with high diagnostic value could supplement diagnosis of this heterogenous group of tumors. The aim of this study was to identify the profiles of circulating miRNA (c-miRNAs) in four groups of common bone and soft tissue sarcomas. Methods: At the time of diagnosis, blood samples were collected from 86 patients: 36 with locally advanced/unresectable/metastatic gastrointestinal stromal tumor (GIST) who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Correspondingly, epigenetics variations in sarcomas mainly encompass three types: DNA methylation, histone modification and non-coding RNA modifications [52,53]. To date, only circulating non-coding RNAs , mainly microRNAs, have been studied in sarcoma liquid biopsy samples [38,40,54,55]. Previous studies have demonstrated that the levels of ctNAs in sarcomas are associated with tumorigenesis, progression and resistance to therapy [40,46,50,54,[56][57][58][59][60].…”
Section: Clinical Applications Of Different Ctnas In Sarcomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, epigenetics variations in sarcomas mainly encompass three types: DNA methylation, histone modification and non-coding RNA modifications [52,53]. To date, only circulating non-coding RNAs , mainly microRNAs, have been studied in sarcoma liquid biopsy samples [38,40,54,55]. Previous studies have demonstrated that the levels of ctNAs in sarcomas are associated with tumorigenesis, progression and resistance to therapy [40,46,50,54,[56][57][58][59][60].…”
Section: Clinical Applications Of Different Ctnas In Sarcomasmentioning
confidence: 99%
“…Increasing evidence indicates that the miRNA expression profile can be used to distinguish many tumor types, including sarcomas [54,167]. miR-1 and miR-113a/b which are regulators of myogenesis, were significantly overexpressed in LMS [58,168].…”
Section: Leiomyosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that non-coding RNAs can be exploited as diagnostic, prognostic and predictive biomarkers. The investigations carried out with GIST report diagnostic miRNA classifiers that distinguish GIST from other sarcomas [80,88,134], identify histological and molecular subtypes [85,98] and define location-specific markers [85]. Of particular clinical interest are the miRNAs associated with relapse risk [84,94,95,98,101,[108][109][110][111][112]135] that may be used to predict tumor recurrence and metastasis.…”
Section: Biomarkersmentioning
confidence: 99%
“…Only few investigators examined the miRNA profiles in serum samples. Distinct serum miRNA expression patterns were observed between GIST patients and healthy controls [134] and miR-518e-5p was identified a classifier for imatinib resistance [119]. Circulating miRNAs or other non-coding RNAs-either packaged in extracellular vesicles or not-may signal tumor recurrence, development of drug resistance and tumor progression or indicate metastasis.…”
Section: Biomarkersmentioning
confidence: 99%